Bioplastics for food packaging. (July 2022) - Shlush, Eden; Davidovich-Pinhas, Maya
Abstract: Background. Packaging materials are responsible for approximately 40% of the produced plastics while food packaging is the number one end user of such materials. Due to the diverse and extensive deleterious effects of conventional plastics on the environment, the food packaging industry is constantly seeking for new alternatives for such materials. Scope and approach. In an attempt to replace petroleum-based plastics and formulate a sustainable solution, new generation of plastic materials termed 'bioplastics' have been developed. The term bioplastic is mostly used to define plastics that can be either bio-based, biodegradable, or both . The current review explores the basic function of food packaging, various types of packaging, the required characteristics and possible processing techniques, and degradation routes of bioplastics. Moreover, the manuscript provides a broad overview of different types of bioplastics utilized in food packaging and their constituent biopolymers, highlighting their distinctive properties and functionalities in relation to their packaging applications. Key findings and conclusions. The food packaging is progressing fast in order to meet the world need for environmentally friendly and sustainable packaging material . These attempts are focused in various fronts which includes (i) improving the performance of natural biodegradable polymers using physical, chemical and enzymatic treatments, (ii) synthesizing new biodegradable polymers, improving the polymer characteristics, and scaling up the processes, (iii) improving the production of bio-based conventional polymers, and (iv) searching for new renewable sources. Highlights: Plastic packaging is accountable for ∼40% of produced plastics, when food packaging is the number one end user. Food packaging is used in order to contain and protect products allowing convenient consumer experience and communication. Bioplastic material can be referred as bio-based, biodegradable, or both. Bioplastic development for food packaging is steadily growing increasing their use as opposed to conventional plastics.